Pengetahuan, Sikap, dan Perilaku Pengelolaan Sampah pada Karyawan di Kampus - N. A., Sangga Saputra; Mulasari, Surahma Asti (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: The existence of garbage are still considered as the something that is not useful and even detrimental to the public. The resulting Bad smell will make people stay away and do not want to handle. Its existence will be a complicated issue and threaten human life, whereas humans also likely to produce even with the passage of time and in line with increasingly consumptive lifestyles that add a lot of garbage resulting. The amount of garbage ever increasing because of the human activities increasingly consumptive need no treatment to reducing piles of garbage. The purpose of research to know correlation between knowledge and attitudes with garbage management behavior on campus X Yogyakarta. Method: This research was observational analytic with cross sectional study design and using the chi-square test, sampling technique using the total sampling and amount of sample is 30 respondens. The instrument that was used, a questionnaire about knowledge and attitudes, behavior while using the checklist. The data analyzing was used Â univariate and bivariate with chi-square test. Results: Based on the results of research conducted on 30 respondents who had bad garbage management behavior as many as 13 people (43.3%) and good garbage management behavior amounted 17 (56.7%). Results of fisher test is obtained no correlation between knowledge and behavior garbage management (p=0.020, RP=0.367, CI; 0.173 to 0.786) and there is nocorrelation between attitude and behavior garbage management (p=0.347, RP=0.779, CI; 0.396 to 1.748). Conclusion: There is a correlation between knowledge and behavior garbage management andthere is no correlation between attitude and behavior garbage management in campus.